New frontiers for sustainable mobility: MaaS (Mobility as a Service) - D’Amico, Annunziata (TeMA - Journal of Land Use, Mobility and Environment, 2023)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of continuously updating emerging topics concerning relationships between urban planning, mobility and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of four parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Urban planning literature review section presents recent books and journals on selected topics and issues within the global scientific panorama. This contribution aims at delving into the issue of sustainable urban mobility through a new mobility paradigm represented by MaaS (Mobility as a Service). Effective and sustainable management of urban transportation activities and services plays an important role within the city to reduce environmental impacts and improve the quality of life for citizens. For the second issue of TeMA Journal, volume n.16, this Review Notes section offers a literature overview on the main aspects of MaaS and its impact on the urban mobility system. It analyzes the potential sustainability benefits of using MaaS in the urban context by citing some interesting and significant journals and books which delved into the topic.